THE EFFECT OF CORPORATE GOVERNANCE ON MARKET PERFORMANCE - Lalu Bintang Indera Praja (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to determine the effect of corporate governance in LQ-45 firms listing on the Indonesian Stock Exchange, which can directly affect the performance of the market mediation. This study was based on LQ-45 member categories and also the companies who had been member of the LQ-45 in the period of 2012-2013. Judgment sampling was employed. The data was collected using a tabulation tested for validity and reliability. The analysis is for the path analysis software testing by SMART PLS. the results found that one received significant negative effect direct corporate governance performance of the market. But the second results found that a positive significant indirect effect among implications of further research, the Indonesian Stock Exchange and the FSA (Financial Service Authority) need to be constantly to promote the capital market and a strong need for effective supervision for the sake of making a stable stock market efficiency.Keywords: Corporate Governance, Capital Structure, Market Performance